Towards a New Modern Ulrich Beck’s Views on the Transformation of Modern Society - Kortava, Shorena (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
A modern German sociologist investigated the transformation of modern society. He took the post-war era of the twentieth century as an indicator of measurement. Ulrikh beck writes that the reason for the transformation of society was the increase in the time that was reduced to labor, the increase in earnings and the better education. The process of individualization has improved the quality of life. The boundaries of social classes have expanded. The classes were transformed into layers. The position of women in society has improved qualitatively. But on the other hand, the competition for them in the labor market has grown. Ulrich Beck writes at the end of his research that the threat to the new society is massive unemployment.